Pendeteksian Penyakit Mulut dan Kuku Pada Sapi dengan Menerapkan Metode Naïve Bayes - Alexius Ulan Bani; Asruddin Asruddin; Asruddin (Journal of Computer System and Informatics (JoSYC), 2022)
The outbreak of the issue in 2022 related to foot and mouth disease which is a viral outbreak experienced in ruminant livestock. This virus outbreak is a virus that is easily transmitted and attacks all types of animals that have even or split nails. The spread of this epidemic is very troubling for the breeder, one of the cattle or cattle breeders. Where as a result of this outbreak, many cattle breeders suffered enormous losses both in terms of finances and the time of raising their livestock. The reason is that many cattle breeders, especially in rural areas, do not know how to treat this disease early and require a large amount of money if the cattle are examined by a veterinarian. Therefore, to make it easier for cattle breeders, we need a way to find out the causes and conditions of cows suffering from mouth and hoof disease based on the symptoms experienced by cows, one of which is by using an expert system. Naive Bayes. The Naïve Bayes method is a probability method by predicting future opportunities based on past experience. As a result, the owner of the cow should treat the cow so as to avoid death and infection to other animals.